2014
DOI: 10.1017/jfm.2014.425
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity of a swept-wing boundary layer to micron-sized discrete roughness elements

Abstract: The receptivity of a laminar swept-wing boundary layer to a spanwise array of circular roughness elements is investigated by means of direct numerical simulations (DNS). The initial amplitude of a steady crossflow mode generated by the shallow roughness elements does not vary strictly linearly with the roughness height, as often assumed. Rather, a fundamental, superlinear dependence of the receptivity amplitude on the roughness height is found. In order to account for shape effects, the roughness geometry is F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 23 publications
3
40
0
Order By: Relevance
“…They commented on the discrepancies with the experimental results of Reibert et al (1996) pointing at possible small imperfections in the application of roughness elements on the model surface (which is very likely in laboratory conditions given the micrometric size of these elements). The problem of receptivity to surface roughness was further investigated by Kurz & Kloker (2014) in a following DNS study. They found that the amplitude of the fundamental stationary mode scales linearly with the roughness height only when the roughness array features null spanwise-averaged shape and flow blockage.…”
Section: Primary Instabilitymentioning
confidence: 99%
“…They commented on the discrepancies with the experimental results of Reibert et al (1996) pointing at possible small imperfections in the application of roughness elements on the model surface (which is very likely in laboratory conditions given the micrometric size of these elements). The problem of receptivity to surface roughness was further investigated by Kurz & Kloker (2014) in a following DNS study. They found that the amplitude of the fundamental stationary mode scales linearly with the roughness height only when the roughness array features null spanwise-averaged shape and flow blockage.…”
Section: Primary Instabilitymentioning
confidence: 99%
“…Radeztsky et al (1999); Bippes (1999); Saric et al (2003); Kurz & Kloker (2014)). As such, notwithstanding the chosen flow control strategy, the used actuators should feature extremely low levels of roughness when installed on the model surface.…”
Section: Plasma Actuators For Cross-flow Instability Controlmentioning
confidence: 99%
“…Note, however, that the strength of the disturbance flow field may depend nonlinearly on roughness parameters such as as the height, as shown by Luchini (2013) for a generic boundary layer and Choudhari & Duck (1996) and Kurz & Kloker (2014b) for swept-wing flow. In the presence of cross-flow instability, such shallow roughness elements induce unstable steady cross-flow modes; a review on related receptivity studies is given in Kurz & Kloker (2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that the strength of the disturbance flow field may depend nonlinearly on roughness parameters such as as the height, as shown by Luchini (2013) for a generic boundary layer and Choudhari & Duck (1996) and Kurz & Kloker (2014b) for swept-wing flow. In the presence of cross-flow instability, such shallow roughness elements induce unstable steady cross-flow modes; a review on related receptivity studies is given in Kurz & Kloker (2014b). A practical application in the scope of LFC is the stabilisation of a three-dimensional boundary layer by the induction of a control mode, as suggested by Saric, Carrillo & Reibert (1998) and the recent associated DNS by Hosseini et al (2013); see also the detailed simulations by Wassermann & Kloker (2002).…”
Section: Introductionmentioning
confidence: 99%